(untitled) (Malaysian Journal of Civil Engineering, 2018)
A study was conducted to treat palm oil mill effluent (POME) using a pilotscale anaerobic-aerobic rotating biological contactor (RBC) . A two-stage RBCsystem was set up in the Environmental Engineering Laboratory at UniversitiTeknologi Malaysia (UTM). The anaerobic RBC was utilised as the primarytreatment unit and the effluent was further treated using an aerobic RBC. Themain aims of this project were to start up the RBC system, to monitor theanaerobic and aerobic system and to investigate the ability of the unit to treatPOME. After full .acclimatisation, continuous flow through the system exhibitedreduction efficiencies of 96%, 71% and 80% for BODs, COD and 5Srespectively.